Bioactive constituents from the leaves of Croton tiglium. (June 2022) - Jiang, Zhi-Yong; Duan, Li-Kun; Feng, Jin-E.; Liu, Chun-Jiang; Li, Xiao-Fei; Li, Yuan; Huang, Chun-Qiu; Shi, Sheng-Li; Zuo, Ai-Xue; He, Hong-Ping
Abstract: Fifteen compounds, including five new phorbol esters (1 -5 ) and ten known metabolites were isolated from the leaves of Croton tiglium . The structures of new compounds 1 -5 were determined by comprehensive analysis of the HRESIMS, IR, 1D and 2D NMR spectral data. The isolates were assayed for their larvicidal and α -glucosidase inhibitory activity; results suggested the new compounds 1 -4 possessed significant insecticidal activity, inhibiting the Plutella xylostella with LC50 values ranging from 0.081 to 0.114 μg/mL, while the sesquiterpenoids 11 and 15 showed noticeable α -glucosidase inhibitory activity with IC50 values of 11.27 and 8.13 μM, respectively. Graphical Abstract: ga1 Highlights: Five new tigliane diterpenoids were isolated from the leaves of Croton tiglium . The new tigliane diterpenoids with unsaturated long-chain esters were obtained in Croton tiglium for the first time. The new tigliane diterpenoids with unsaturated long-chain esters were firstly found to possess significant larvicidal activity. The isolated sesquiterpenoids were found to possess remarkable α -glucosidase inhibitory activity.